Effects of bank mergers and acquisitions on revenue efficiency during the pre-merger and post-merger periods in the Malaysian banking sector - Kamarudin, Fakarudin (2011)
The objective of this study is to identify the effects of the mergers and acquisitions (M&As) on revenue efficiency over the pre-merger and post-merger periods in the Malaysian banking sector. The main goal of bank M&As is to enhance and maximise the profit efficiency. Nevertheless, revenue inefficiency could contribute to lower profit efficiency when banks produce too few outputs for the given inputs, and produce too little of a high-priced output and too much of a low-priced output. This finding is supported by previous studies carried out in developed and developing countries which practice voluntary and forced M&As (Ariff and Can, 2008 and Houston et al., 2001). The study also examines the potential bank specific determinants that influence revenue efficiency during post-merger period. Although several studies have identified the potential bank specific and macroeconomic determinants that could contribute to higher level of efficiency to reduce revenue inefficiency, the results remain inconclusive. The data gathered in this study are divided into two event windows; namely, premerger period (1995-1996) and post-merger period (2002-2009). The data collected included the year of mega-merger 2000 in which M&As took place in Malaysia (Sufian, 2009). To represent the Malaysian banking sector, a sample of 34 local and foreign commercial banks including the control group of banks were selected to participate in the study. The level of revenue efficiency was measured using Data Envelopment Analysis (DEA) method which applied the intermediation approach. The data were tested by using the parametric (t-test) and non-parametric Mann-Whitney (Wilcoxon) and Kruskal-Wallis tests. The results showed that revenue efficiency in Malaysian banking sector did not improve during the post-merger period. The determinants that could improve the revenue efficiency in Malaysian banking sector during the post-merger period were identified using Multivariate Regression Analysis (MRA). The analysis applied the Generalized Least Square (GLS) method consisting of Fixed Effect Model (FEM) and Random Effect Model (REM) run by Hausman test. Three bank specific determinants were found to influence the improvement of revenue efficiency: size of bank, market power and management quality. Another factor, the inflation factor (macroeconomic) was also found to influence the improvement of the revenue efficiency in Malaysian banking sector during the post-merger period. The research concludes that findings from studies on M&As on revenue efficiency in the Malaysian banking sector provide guidance, better information and fill in the gap in current literature which can benefit the regulators, the banking sector itself, investors and academics when they make decisions on future M&As.